A Historical Perspective on Student Affairs Professionals' Use of Digital Technology. Issue 155 (September 2016) - Cabellon, Edmund T.; Payne‐Kirchmeier, Julie
Abstract : This chapter provides a historical perspective of student affairs professionals' use of digital and social technologies in their work on college campuses. The purpose of the chapter is to describe how digital technology tools have evolved since 2005, demonstrate how student affairs technology shifted and changed during this time, and shape student affairs administrators' future technology use.